Polylactide Used as Filment in 3d Printing – Part 2: TG-DTG, DSC and DRIFT investigations - Grabowska, Beata; Skowron, Mateusz; Kaczmarska, Karolina (Journal of Casting & Materials Engineering, 2023)
A series of structural and thermal analysis research (TG-DTG, DSC, DRIFT) were performed for the samples of polylactide (PLA), which is commonly used in additive technologies as a structural material. In total four materials were considered, including two containing dyes with different colors, a material made of PLA recyclate and a graphene-modified PLA material. It was noted that PLA material reinforced with graphene phase (GRAFYLON®) retains the best thermal properties (TG-DTG), which results in wider possibilities of its processing, including further modification and usability in manufacturing vehicle structural elements. Recycled PLA material (ALFA+W) was characterized by a higher melting point (Tp) by more than 20oC than other samples (DSC analysis), so it can be more useful in the production of structural elements operating, as well as used at elevated temperatures.